Calidad Microbiológica Del Agua En La Cuenca Media Del Río Usumacinta, Tabasco, México - Durán-Mendoza, Temani; González-de la Cruz, José Ulises; González-Pérez, Manuel; Pérez-Sánchez, Carolina del Carmen; Gómez, Raúl Hernández; Cuenca-Soria, Carlos Alberto; Cruz-Leyva, María Concepción de la (European Scientific Journal, ESJ, 2018)
Some species of pathogenic bacteria such as Salmonella, Escherichia coli, Shigella, among others, are a threat to the ichthyofauna that lives in freshwater rivers. This threat extends to the human population that develops various activities in this environment. Food products derived from these activities can affect consumers as well. Therefore, the objective of this research was to evaluate the microbiological quality of water in the middle basin of the Usumacinta River, Tabasco, Mexico. A total of 63 water samples were collected in 12 sampling sites: 36 in the dry season and 27 in the rainy season in 2013. The microbiological analysis was carried out according to Mexican standards. The highest concentration of CT was detected in Usumacinta (Usu) (130 NMP / 100mL) during the dry season and in Petunia (Pet) (240 NMP / 100mL) during the rainy season. The highest concentration of CF was detected in the water plant (Pa), Pet and Estapilla (Est) (34 NMP / 100mL), during the rainy season. The results of CT and CF registered significant differences in the Colony Forming Units (CFU), due to seasonality (p <0.05). Thus, they were not significant due to the effect of the sampling sites (p <0.05). Also, 284 putative strains of enterobacteria isolated and identified mainly Escherichia sp and Salmonella sp in the two studied seasons. These results are one of the first evidences of the microbiological quality of water in the middle basin of the river Usumacinta, Mexico.